THE EFFECT OF ISLAMIC HUMAN DEVELOPMENT INDEX ON POVERTY LEVEL IN BIREUEN DISTRICT PERIOD 2000-2017 - Muhammad Reza; Hijri Juliansyah; Yulius Dharma (LPPM Universitas Malikussaleh, 2018)
The study entitled